Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Solve for [tex]x[/tex]:

[tex]\[ -48(1 + 0.5x) + 2x^2 = 8x\left(\frac{1}{4}x + 3\right) \][/tex]


Sagot :

To solve the equation [tex]\(-48(1 + 0.5x) + 2x^2 = 8x \left(\frac{1}{4}x + 3 \right)\)[/tex], we need to follow these steps:

1. Expand both sides of the equation:
- Expand the left-hand side: [tex]\(-48(1 + 0.5x) + 2x^2\)[/tex]
[tex]\[ -48 \cdot 1 - 48 \cdot 0.5x + 2x^2 = -48 - 24x + 2x^2 \][/tex]
- Expand the right-hand side: [tex]\(8x \left(\frac{1}{4}x + 3\right)\)[/tex]
[tex]\[ 8x \cdot \frac{1}{4}x + 8x \cdot 3 = 2x^2 + 24x \][/tex]

So the expanded equation is:
[tex]\[ -48 - 24x + 2x^2 = 2x^2 + 24x \][/tex]

2. Move all terms to one side to set the equation to 0:
Subtract [tex]\(2x^2\)[/tex] and [tex]\(24x\)[/tex] from both sides of the equation:
[tex]\[ -48 - 24x + 2x^2 - 2x^2 - 24x = 2x^2 + 24x - 2x^2 - 24x \][/tex]
This simplifies to:
[tex]\[ -48 - 48x = 0 \][/tex]

3. Solve for [tex]\(x\)[/tex]:
Add [tex]\(48\)[/tex] to both sides of the equation:
[tex]\[ -48x = 48 \][/tex]
Divide both sides by [tex]\(-48\)[/tex]:
[tex]\[ x = -1 \][/tex]

So, the solution to the equation [tex]\(-48(1 + 0.5x) + 2x^2 = 8x \left(\frac{1}{4}x + 3 \right)\)[/tex] is:
[tex]\[ x = -1 \][/tex]